2017
DOI: 10.1017/jfm.2017.121
|View full text |Cite
|
Sign up to set email alerts
|

Thermal convection with mixed thermal boundary conditions: effects of insulating lids at the top

Abstract: The effects of insulating lids on the convection beneath were investigated experimentally using rectangular convection cells in the flux Rayleigh number range 2.3 × 10 9 Ra F 1.8 × 10 11 and cylindrical cells in the range 1.4 × 10 10 Ra F 1.2 × 10 12 with the Prandtl number Pr fixed at 4.3. It is found that the presence of the insulating lids leads to reduction of the global heat transfer efficiency as expected, which primarily depends on the insulating area but is insensitive to the detailed insulating patter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 23 publications
2
41
0
Order By: Relevance
“…The two latter numerical studies have shown that from a certain characteristic patch size, the effect on the flow dynamics becomes almost negligible in the turbulent regime. The three-dimensional work by Bakhuis et al (2017) also showed that the effect of the shape of these patches is small, something which at first glance contradicts Cooper et al (2013) and Wang et al (2017). Therefore, a cross-over between two regimes must exist, one where large adiabatic patches which significantly affect the flow topology and another where small adiabatic patches whose effect is only present very close to the plates must exist.…”
Section: Futurementioning
confidence: 98%
See 4 more Smart Citations
“…The two latter numerical studies have shown that from a certain characteristic patch size, the effect on the flow dynamics becomes almost negligible in the turbulent regime. The three-dimensional work by Bakhuis et al (2017) also showed that the effect of the shape of these patches is small, something which at first glance contradicts Cooper et al (2013) and Wang et al (2017). Therefore, a cross-over between two regimes must exist, one where large adiabatic patches which significantly affect the flow topology and another where small adiabatic patches whose effect is only present very close to the plates must exist.…”
Section: Futurementioning
confidence: 98%
“…To help understand these issues, Wang et al (2017) performed an experimental study of Rayleigh-Bénard flow with mixed thermal boundary conditions, insulating a fraction of the top plate with adiabatic patches. They used two experimental set-ups: a rectangular tank and a cylindrical tank, in an attempt to make their results as general as possible.…”
Section: Overviewmentioning
confidence: 99%
See 3 more Smart Citations